THE INFLUENCE OF ORGANIZATIONAL COMMUNICATION CLIMATE ON EMPLOYEE PERFORMANCE IN BANDUNG REGIONAL REVENUE MANAGEMENT AGENCY - Lusiawati, Ira (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
This study examines the problem of not optimal employee performance at the Regional Income Management Agency in the city of Bandung. Problems in the Organizational Communication Climate that have not been optimally carried out on Employee Performance at the Regional Revenue Management Agency in the city of Bandung. Quantitative approach is used in this study to determine the relationship between variables through hypothesis testing in a population. The research method used is the Explanatory Survey Method with data collection techniques using a five-scale questionnaire. The number of respondents was 167 people, taken by simple random sampling from members of the population of 286 people at the Bandung Regional Revenue Management Agency. Data processing techniques use Structural Equation Modeling (SEM). Based on the results of the research on exogenous variables, namely the Organizational Communication Climate variable on Employee Performance as an endogenous variable, it is significant. In detail, the results of this study indicate that: The influence of the Organizational Communication Climate variable (X) which consists of: Trust Factor, Participation Factor in Decision Making, Honesty Factor, Openness Factor in Downward Communication, and Listening Factor in Upward Communication has an effect of 0.26 and significant by 2.00 on Employee Performance (Y). Research findings on the variables of Organizational Communication Climate, namely Ethos Factors and Relationship Factors, as a whole the research on the influence of Organizational Communication Climate on employee performance has had a positive influence on the Regional Revenue Management Board of the city of Bandung.